2015
DOI: 10.1108/mrr-07-2013-0169
|View full text |Cite
|
Sign up to set email alerts
|

Workplace spirituality and stress: evidence from Mexico and US

Abstract: 2015),"The mediating role of burnout on the relationship of emotional intelligence and self-efficacy with OCB and performance", Management Research Review, Vol. 38 Iss 1 pp. 2-28 http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
99
0
8

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(107 citation statements)
references
References 44 publications
0
99
0
8
Order By: Relevance
“…A large number of studies prove such positive connections (for a meta-analysis, see Allan et al, 2019). Meaningful work is related to a general sense of meaning in life (Steger and Dik, 2009;Steger et al, 2012;Duffy and Dik, 2013;Schnell, 2018), work engagement (Höge and Schnell, 2012), turnover intentions (Arnoux-Nicolas et al, 2016), depression (Steger et al, 2012;Daniel, 2015), socio-moral organizational climate (Schnell et al, 2013;Höge and Weber, 2018;Schnell, 2018), job satisfaction (Duffy and Dik, 2013;Duffy et al, , 2014Allan et al, 2018;Schnell, 2018;Rothausen and Henderson, 2019), and health experience (Lease et al, 2019), although for the latter there are indications of gender-specific differences (Dich et al, 2019).…”
Section: Why and When Meaningful Work Makes Sensementioning
confidence: 99%
“…A large number of studies prove such positive connections (for a meta-analysis, see Allan et al, 2019). Meaningful work is related to a general sense of meaning in life (Steger and Dik, 2009;Steger et al, 2012;Duffy and Dik, 2013;Schnell, 2018), work engagement (Höge and Schnell, 2012), turnover intentions (Arnoux-Nicolas et al, 2016), depression (Steger et al, 2012;Daniel, 2015), socio-moral organizational climate (Schnell et al, 2013;Höge and Weber, 2018;Schnell, 2018), job satisfaction (Duffy and Dik, 2013;Duffy et al, , 2014Allan et al, 2018;Schnell, 2018;Rothausen and Henderson, 2019), and health experience (Lease et al, 2019), although for the latter there are indications of gender-specific differences (Dich et al, 2019).…”
Section: Why and When Meaningful Work Makes Sensementioning
confidence: 99%
“…Furthermore, it was observed that workplace spirituality leads to increase feeling toward others and it acts as a weapon that attracts and retain employees within the organization Jena & Pradhan, 2018). Enhancing trust among people (Neck & Milliman, 1994) and increasing interconnectedness (Daniel, 2015) create a more motivated organizational working environment as benefits of workplace spirituality. Workplace spirituality is very much important not only because it leads to enhance personal growth but also to increase the psychological contract between employers and employees (Ahiauzu & Asawo, 2012).…”
Section: Workplace Spiritualitymentioning
confidence: 99%
“…During the last few years, WPS has become an emerging area of investigation in organizational research (Ashmos & Duchon, 2000;Chawla & Guda, 2013;Daniel, 2015). Many organizational studies have reported significant effect of employees' WPS on many positive work attitudes and behaviors such as job commitment (Chawla & Guda, 2010), individual well-being (Mackenzie, Rajagopal, Meilbohm, & Lavizzo-Mourey, 2000), work unit performance (Duchon & Plowman, 2005), and organizational performance (Fry & Matherly, 2006).…”
Section: Workplace Spirituality and Prosocial Rule-breakingmentioning
confidence: 99%